2016
DOI: 10.1117/1.oe.55.11.116106
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion measurement of microstructured negative curvature hollow core fiber

Abstract: Abstract. We present measurements of the dispersion of two negative curvature fibers at and around 1 μm. These fibers are suitable for beam delivery of both high power and ultrashort pulse lasers with one designed to operate at 1030 nm and the other designed for dual wavelength delivery at 515 and 1030 nm. Both fibers were found to exhibit anomalous dispersion measured to be 2.17 AE 0.25 ps nm −1 km −1 for the fundamental mode rising to 4.69 AE 0.17 ps nm −1 km −1 for the first-order mode in the 1030-nm fiber.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The guidance mechanism of NCHCFs is based on the anti-resonance effect in glass core walls that act as a Fabry-Perot cavity, and the anti-resonance effect is strengthened through inhibition of the coupling effect to reduce the transmission attenuation and enhance the operational bandwidth. (5)(6)(7) A guiding light in a large hollow air-filled core endows NCHCFs with the favorable properties of high power transmission, ultralow dispersion, a large bandwidth, and a simple structure. (8)(9)(10)(11) In 2020, (12) we used a combination of an NCHCF and a gold-plated graded-index fiber to fabricate a hollow-core photonic crystal fiber sensor and we analyzed the sensing properties of the NCHCF sensor by measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The guidance mechanism of NCHCFs is based on the anti-resonance effect in glass core walls that act as a Fabry-Perot cavity, and the anti-resonance effect is strengthened through inhibition of the coupling effect to reduce the transmission attenuation and enhance the operational bandwidth. (5)(6)(7) A guiding light in a large hollow air-filled core endows NCHCFs with the favorable properties of high power transmission, ultralow dispersion, a large bandwidth, and a simple structure. (8)(9)(10)(11) In 2020, (12) we used a combination of an NCHCF and a gold-plated graded-index fiber to fabricate a hollow-core photonic crystal fiber sensor and we analyzed the sensing properties of the NCHCF sensor by measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Further numerical studies on the simplified AR-HCF structure revealed that single-mode performance can be achieved by phase matching the HOMs to the cladding modes [160]. Another advantage of the simplified AR-HCF is the relatively flat dispersion profile around the zero-dispersion wavelength [168]. As described in Chapter 2.2, dispersion relates to the temporal delay between the high and low frequency components in a pulse.…”
Section: Antiresonant Hollow-core Fibermentioning
confidence: 99%